Analisis Makna Hidup dan Dukungan Sosial terhadap Resiliensi Remaja Penyintas Percobaan Bunuh Diri di Kota Makassar (Perspektif Teori Grotberg) - Yusuf, Nur Usna Rezky Putri; Sinring, Abdullah; Harum, Akhmad (IAIN Kudus, 2026)
The Dynamics of Resilience in Adolescent Suicide Attempt Survivors: A Case Study of Meaning in Life and Social Support from Grotberg's Perspective. This study aims to analyze the meaning in life among adolescent suicide attempt survivors, explore the forms of social support they receive, and describe the role of meaning in life and social support in shaping resilience based on Grotberg's theory. This study uses a qualitative approach with a case study design. Informants were selected through purposive sampling, consisting of two adolescent suicide attempt survivors as primary informants and a psychologist as a supporting informant. Data collection was conducted over a period of 3 months through in-depth interviews, observation, and documentation studies, which were analyzed using MAXQDA software. The validity of the data in this study was maintained through source triangulation by comparing data from adolescent suicide attempt survivors and supporting informants (psychologists), as well as technique triangulation through in-depth interviews, observation, and documentation studies. To maintain the accuracy of sensitive data, the researcher conducted member checking. The results of the study show that each adolescent suicide attempt survivors has a different experience in interpreting life after suicide attempts. Informants interpret life as a second chance to improve relationships with family, as well as how to find meaning in life through personal goals and the desire to help others based on previous experiences.The social support received is also diverse, ranging from emotional support from family, acceptance from peers, and community. These experiences strengthen the aspects of I Have, I Am, and I Can. These findings can be used as a basis for counselors in designing resilience-based preventive and curative guidance and counseling services for adolescents.Keywords: Meaning in Life, Social Support, Resilience, Grotberg's Theory.